ASPECTOS FISIO-COGNITIVOS COM A UTILIZAÇÃO DA TORRE DE HANÓI NO ENSINO FUNDAMENTAL - Leonardo Almeida Cavalcanti; Ademir Lentz; Marcia Garcia Lopes (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2014)
This research is the application and study of the Tower of Hanoi to characterize the action level and the level of understanding of the game. The participants in the experiment were a total of 10 female students from 13 to 15 years old. Data were collected through recording the numbers of movements in second, errors and answers of 03 questions. From the physiological and intellectual development of the studied people, can be affirmed that there is a great practical distance between perform and understand a given task, there is a production of intellect that resulting in thought. Which can improve the planned and intentionally behavior used to solve a task, reflecting the strategic level of the subject. The results suggest an effect in the action of learning, but there was no understanding of learning.